7 Characterisations of heart function and cardiac stem cells in the animal model of human muscular dystrophy: mdx mice. Issue 20 (23rd September 2011) - Hsiao, L C; Carr, C; Clarke, K
Abstract : Duchenne muscular dystrophy (DMD), an X-linked recessive disease, is characterised by a systemic lack of dystrophin protein in the sarcolemma, affecting skeletal and cardiac muscles. Current therapies have increased life span in DMD patients, but this has led to the majority of surviving patients developing dilated cardiomyopathy. Recently, stem cell-based therapy has emerged as a promising approach to treat cardiovascular diseases. However, little is known about the characteristics of endogenous cardiac stem cells in patients with DMD. This study aimed to measure heart function using high field MRI and characterise cardiac stem cells in the wild-type (n=8) and mdx mouse (n=9), an animal model of human muscular dystrophy, at an average age of 20 months. Hearts from mdx mice had increased right ventricular end-diastolic and end-systolic volumes and reduced left and right ventricular ejection fractions. Endogenous cardiac stem cells were isolated from heart biopsy samples via the formation of cardiospheres and characterised using flow cytometry. Explant-derived cells (EDCs) isolated from mdx hearts formed significantly fewer cardiospheres per 30 000 EDCs than those from wild-type hearts (19±2.8 vs 26.7±5.3, p<0.01), but generated more cardiosphere-derived cells (CDCs) (2.9±1.7×105 vs 1.4±0.5×105, p<0.05). Approximately 70% of CDCs expressed sca-1 in both groups. Interestingly, CDCs from mdx mice exhibited higher expression of c-kit (16.1±6.3% vs 8.9±3.4%, p<0.05) and lower expression of CD90 (44.3±15.8% vs 77.9±10.6%, p<0.01) compared with cells from wild-type hearts. In conclusion, the mdx mouse, a disease model of human DMD, is associated with impaired cardiac function and had increased c-kit and decreased CD90-expressing CDCs.